Targeting in Complex Emergencies: South Sudan Country Case Study - Maxwell, Daniel; Burns, John (Tufts Archival Research Center, 2005)
The population of Southern Sudan was caught in a civil war from 1983 to 2005. During the war, several major famines led to a massive Food relief intervention by the World Food Programme â intervention that continues to the present. Much of this food was delivered to vulnerable people by air drops, with the actual targeting of assistance on the ground left to local leaders and traditional authorities. The main objective of targeting was to minimize exclusion.